The hydrological impact of geoengineering in the Geoengineering Model Intercomparison Project (GeoMIP). Issue 19 (15th October 2013) - Tilmes, Simone; Fasullo, John; Lamarque, Jean‐Francois; Marsh, Daniel R.; Mills, Michael; Alterskjær, Kari; Muri, Helene; Kristjánsson, Jón E.; Boucher, Olivier; Schulz, Michael; Cole, Jason N. S.; Curry, Charles L.; et al.
<x xml:space="preserve">Abstract</x> [1] The hydrological impact of enhancing Earth's albedo by solar radiation management is investigated using simulations from 12 Earth System models contributing to the Geoengineering Model Intercomparison Project (GeoMIP). We contrast an idealized experiment, G1, where the global mean radiative forcing is kept at preindustrial conditions by reducing insolation while the CO2 concentration is quadrupled to a 4×CO2 experiment. The reduction of evapotranspiration over land with instantaneously increasing CO2 concentrations in both experiments largely contributes to an initial reduction in evaporation. A warming surface associated with the transient adjustment in 4×CO2 generates an increase of global precipitation by around 6.9% with large zonal and regional changes in both directions, including a precipitation increase of 10% over Asia and a reduction of 7% for the North American summer monsoon. Reduced global evaporation persists in G1 with temperatures close to preindustrial conditions. Global precipitation is reduced by around 4.5%, and significant reductions occur over monsoonal land regions: East Asia (6%), South Africa (5%), North America (7%), and South America (6%). The general precipitation performance in models is discussed in comparison to observations. In contrast to the 4×CO2 experiment, where the frequency of months with heavy precipitation intensity is increased by over 50% in comparison to the control, a reduction of up to 20% is simulated in G1. These changes in precipitation in both total amount and frequency of extremes point to a considerable weakening of the hydrological cycle in a geoengineered world.